The NHS Diabetes Prevention Programme: an observational study of service delivery and patient experience - Rhiannon E. Hawkes; Elaine Cameron; Sarah Cotterill; Peter Bower; David P. French (BMC, 2020)
Abstract Background The NHS Diabetes Prevention Programme (NHS-DPP) is a nine-month, group-based behavioural intervention for adults in England at risk of developing Type 2 diabetes. Four independent providers were commissioned to deliver versions of the NHS-DPP, in line with NHS England specifications. This observational study maps NHS-DPP delivery in routine practice against the NHS specification, and compares service delivery with observed patient experiences. Methods Researchers observed service delivery across eight complete NHS-DPP courses (118 sessions, median 14 sessions per course), consenting 455 participants (36 staff, 398 patients, 21 accompanying persons). Key features of NHS-DPP delivery were described using the Template for Intervention Description and Replication (TIDieR) framework. Researchers wrote detailed field notes during each session, including observations of patient experience. Field notes were content analysed; instances of positive and negative experiences were labelled and grouped into categories. Researchers used a novel method of comparing observed patient experiences to variations in programme delivery. Results Delivery broadly followed NHS England's specification and the plans set out by providers. Deviations included the scheduling and larger group sizes in some sessions. There was variation in the type and format of activities delivered by providers. Positive patient experiences included engagement, satisfaction with the programme, good within-group relationships and reported behavioural changes. Negative experiences included poor scheduling, large groups, and dissatisfaction with the venue. Where more interactive and visual activities were delivered in smaller groups of 10-15 people with good rapport, there were generally more instances of positive patient experiences, and where there were structural issues such as problems with the scheduling of sessions, poor venues and inadequate resources, there tended to be more negative patient experiences. Conclusions Addressing issues that we have identified as being linked to negative experiences with the NHS-DPP could increase uptake, reduce patient drop-out and increase the overall effectiveness of the programme. In particular, modifying structural aspects of the NHS-DPP (e.g. reliable session scheduling, reducing group sizes, enough session resources) and increasing interaction appear particularly promising for improving these outcomes.